THE INFLUENCE OF INFORMATION ASYMMETRY, COMPANY SIZE, AND LEVERAGE ON EARNINGS MANAGEMENT AT HANSON INTERNATIONAL TBK - Aulia Rinaldi; Wahyuddin (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This research aims to determine the Influence of Information Asymmetry, Company Size, and Leverage on Earnings Management at Hanson International Tbk. The data used in this study are secondary data from PT. Hanson International Tbk for the first quarter of 2005 to the fourth quarter of 2022, resulting in 72 observations. The method used to analyze the relationship between independent variables and dependent variables is the multiple linear regression analysis method with the assistance of SPSS software. The results show that partially, information asymmetry has a positive and significant effect on earnings management at PT. Hanson International Tbk. This indicates that the higher the information asymmetry, the higher the company's earnings management will be. Company size has a positive and significant effect on earnings management at PT. Hanson International Tbk. This indicates that the larger the company size, the higher the company's earnings management will be. Leverage has a positive and significant effect on earnings management at PT. Hanson International Tbk. This indicates that the higher the leverage, the higher the company's earnings management will be. Simultaneously, Information asymmetry, company size, and leverage have a positive and significant effect on earnings management at PT. Hanson International Tbk. This indicates that the higher the information asymmetry, company size, and leverage, the higher the company's earnings management will be.